2015
DOI: 10.1097/mop.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

The role of cilia in the pathogenesis of cystic kidney disease

Abstract: Purpose of review Primary (immotile) cilia are specialized organelles present on most cell types. Almost all of proteins associated with a broad spectrum of human cystic kidney diseases have been localized to the region in or around the cilia. Abnormal cilia structure and/or function have been reported in animal models and human cystic kidneys. The goal of this review is to discuss current understanding of the mechanisms by which abnormal genes/proteins and cilia interact to potentially influence renal cystoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Research on abnormal cilia mechano-function in the kidneys has centered around flow-induced changes in intracellular Ca 2+ ; when either PC-1 or PC-2 is altered, the expected elevation in intracellular Ca 2+ is abolished, thereby altering downstream signaling cascades and activating pro-cystogenic pathways. Interestingly, this has been observed in a cilia-less mutant renal cell line, orpk, suggesting that a loss of protein function or a loss of the cilia structure dysregulates Ca 2+ entry into the cell and promotes aberrant tissue maintenance [ 38 ]. Similarly, cilia on vascular endothelial cells are also responsible for detecting fluid shear stress in order to maintain blood pressure.…”
Section: Calcium and Ciliary Signal Transduction: Sensory Functionmentioning
confidence: 99%
“…Research on abnormal cilia mechano-function in the kidneys has centered around flow-induced changes in intracellular Ca 2+ ; when either PC-1 or PC-2 is altered, the expected elevation in intracellular Ca 2+ is abolished, thereby altering downstream signaling cascades and activating pro-cystogenic pathways. Interestingly, this has been observed in a cilia-less mutant renal cell line, orpk, suggesting that a loss of protein function or a loss of the cilia structure dysregulates Ca 2+ entry into the cell and promotes aberrant tissue maintenance [ 38 ]. Similarly, cilia on vascular endothelial cells are also responsible for detecting fluid shear stress in order to maintain blood pressure.…”
Section: Calcium and Ciliary Signal Transduction: Sensory Functionmentioning
confidence: 99%
“…In autosomal dominant PKD, the most common form of PKD, mutations are commonly found in two genes: polycystin 1, a large transmembrane protein associated with primary cilia; and polycystin 2, a TRP-family channel. The orthodoxy is thus that defects in the primary cilium of renal cells confers problems with apicobasal polarity (Yoder 2007;Dell 2015), although the subtlety and complexity of the connection between cilia and PKD is only now becoming clear (Dell 2015). Unfortunately, while Drosophila has a gene similar to Pkd2, it lacks primary cilia in most cells, so a direct renal model is not available.…”
Section: Modeling Disease Processesmentioning
confidence: 99%
“…Both JS and MGS are inherited in an autosomal recessive pattern and have been categorised alongside ADPKD, ARPKD and NPHP as 'ciliopathies', a term which denotes defects in primary cilia [20,21]. Primary cilia have been implicated in kidney development and disease and are linked to proteins that are associated with cystic renal diseases, including the diseases mentioned above [22]. Signalling via the primary cilium is also thought to be a crucial process and evidence has found that defects in cilia can impact cilia-associated signalling pathways, including Wnt signalling [23].…”
Section: The Clinical Symptoms Of Genetically Inherited Chronic Kidnementioning
confidence: 99%